Farmers’ benefit from activities of some agricultural organizations in Kafr El-Sheikh and Gharbia governorate - Bazina, Tiesseer Kassem; Hegazy, Hassan Mohamed Nabawy; Hlil, Huda Moustafa; Ghallab, Mohamed Mohamed Helmy (Journal of Humanities & Social Sciences, 2022)
This study aimed at identifying the level of farmers’ benefit from activities of agricultural organizations: the agricultural cooperative, the agricultural extension Center, and the agricultural bank, identifying relationships between the studied independent variables and the farmers’ benefit from the activities carried out by these organizations, identifying the variables that most contribute to explaining the variance in farmers’ benefit from the activities. Data were collected through personal interviews using a pretested schedule from a random sample of 165 respondents and appropriate statistical methods were used to obtain the following results. - That 38.2%, 46.7%, and 57.6% of the respondents believe that their benefit from activities carried out by the Agricultural Cooperative, the Extension Center, and the Agricultural Bank is average, respectively. - The ten independent variables together explain 15.4%, 28.9%, and 23.7% of the total variance in the respondents’ benefit from activities carried out by the three organizations, respectively. - Two variables explain 11.1% and 16.5% of the variance in the benefit from activities carried out by the Agricultural Cooperative and the Agricultural Bank, respectively, and six variables explain 27% of the variance in the benefit from activities carried out by the Extension center. - The most important problem that limited Farmers’ benefit from activities of the agricultural cooperatives was the lack of production requirements (seeds- fertilizers- pesticides) in a suitable time, for the extension center was holding seminars and extension meetings at inappropriate times, and for the agricultural bank was guarantees and conditions for obtaining loans are complex and numerous. - The most important suggestions by farmers for facing problems that limit their benefit from activities of the agricultural cooperative was providing good and supported production supplies to farmers at the right times and in sufficient quantities, for the extension center was Providing publications and extension bulletins at the right times, and for the agricultural bank was extending the repayment period of loans following the conditions of the farmers.